2015
DOI: 10.1371/journal.pone.0131336
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profile in Penile Cancer Revealed by Next-Generation Small RNA Sequencing

Abstract: Penile cancer (PeCa) is a relatively rare tumor entity but possesses higher morbidity and mortality rates especially in developing countries. To date, the concrete pathogenic signaling pathways and core machineries involved in tumorigenesis and progression of PeCa remain to be elucidated. Several studies suggested miRNAs, which modulate gene expression at posttranscriptional level, were frequently mis-regulated and aberrantly expressed in human cancers. However, the miRNA profile in human PeCa has not been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 89 publications
4
39
1
Order By: Relevance
“…The first NGS analysis of small RNAs expressed in penile cancers was published in 2015. Interestingly, the TGF-β signaling pathway was among the top enriched pathways predicted to be targeted by miRNAs differently expressed in penile cancer tissues compared with matched adjacent non-cancerous tissues [290]. Furthermore, TGFB3 and TGFBR2 were found within the top pathways involving miRNA-targeted genes disrupted in penile cancer [291].…”
Section: Penile Cancermentioning
confidence: 99%
“…The first NGS analysis of small RNAs expressed in penile cancers was published in 2015. Interestingly, the TGF-β signaling pathway was among the top enriched pathways predicted to be targeted by miRNAs differently expressed in penile cancer tissues compared with matched adjacent non-cancerous tissues [290]. Furthermore, TGFB3 and TGFBR2 were found within the top pathways involving miRNA-targeted genes disrupted in penile cancer [291].…”
Section: Penile Cancermentioning
confidence: 99%
“…In addition, they reveal new signaling pathways and therapeutic molecular targets, correlated with carcinogenesis (Weidan et al, 2017). In PC, the first large-scale study with microRNAs analysis was conducted by Zhang et al, (2015), and some differentially expressed microRNAs were identified, such as miR-107, and miR-223-3p. These micro RNAs were described related with metastasis, invasion, transport, and colonization in cancer (Gao et al, 2016;Hu et al, 2016;Markou et al, 2016;Mavrakis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one half of microRNA (miR) genes are distributed at unstable sites of the genome, including fragile sites of chromatin and cleavage sites (2,3). There is a significant difference in the expression level of miRs in cancerous tissue and normal tissue (4). Based on their diversity and wide distribution throughout the genome, miRs may serve as an important tumor diagnostic method (5).…”
Section: Introductionmentioning
confidence: 99%